Perceived stress and readiness to undertake biodebridement in the group of nurses undertaking prevention and treatment of chronic wounds - Przybek Mita, Joanna; Bazaliński, Dariusz; Sztembis, Rafał; Kuberka, Izabela; Więch, Paweł (Frontiers in Public Health, 2022)
Introduction Stress as the body's response to adverse stimulus is recognized as one of the key problems in basic and clinical neurological studies. Stress is an indispensable component of modern nursing with its low doses being desirable, however, prolonged stress is detrimental to health increasing the risk of chronic disease i.e., hypertension, cardiovascular diseases, electrolyte disturbances, occupational burnout, depression, anxiety disorders. The implementation of certain techniques and therapeutic methods may have a stressful effect from the point of view of practice and the patient's condition. Methods The authors undertook the study to assess the intensity of the perceived stress in the group of nurses dealing with wound care in the perspective of implementing wound debridment using Lucilia sericata larvae. The study group consisted of 290 nurses specialized in chronic wounds undergoing training at the Postgraduate Training Center of Nurses and Midwives in Rzeszów, out of the entire group of 1.136 individuals participating in training courses organized in Poland in 2020–2021. The study used the diagnostic survey method, the research tool was a scientific research protocol consisting of tools (MDT perception questionnaire, perceived stress scale (PSS-10). Results Certain differences in the level of stress in the study sample were observed between age categories, but they were not statistically significant. The greatest differences between the levels of stress in the study sample were observed between people who completed treatment courses and those who did not complete these courses. The higher the stress level, the lower the willingness to undertake such therapy. The analysis of grouped data leads to interesting observations. There were statistically significant differences in the score in the MDT10 scale in the categories of people with different stress levels. The highest readiness to implement MDT was observed in the category of people with the lowest perceived level of stress. Conclusions The level of professional experience related to postgraduate education increases opportunities addressing new professional challenges. The level of perceived stress may influence decisions related to the use of biological therapy. The higher the level of stress, the lower the readiness to undertake MDT.